The decreasing activity of white tea and green tea on smokers lipids profile - Kushargina, Rosyanne; Rimbawan, Rimbawan; Setiawan, Budi; Rohdiana, Dadan (Jurnal Penelitian Teh dan Kina, 2015)
Smoking habit have many negative effect, including increased lipids profile. Researching on the effects of tea on lipids profile on smokers has been carried out using green tea. Research using white tea has been limited, therefore, this study aimed to analyze the effect of white tea than green tea on lipids profile in smokers, using paired sample of clinical trials design. The subjects were medium smokers (11-21 cigarettes/day) aged 30-45 years and have milddyslipidemia. Each subject was asked to drink tea in two times. Firstly, all subjects were asked to drink 3 x 200 ml white tea/day for 28 days. Secondly, treatment will be start after two weeks washout period, and they were asked to drink 3 x 200 ml of green tea/day for 28 days. Lipids profile (trigliserida (TG); cholesterol total (TC); low density lipoprotein-cholesterol (LDL-C)) of blood serum has been measured four times, at pre-post intervention of white tea and at pre-post intervention of green tea. The lipids profile were significantly decreased after white tea intervention (paired sample t-test, p<0,05). After green tea intervention,the lipids profile were decreased but significant (paired sample t-test, p<0,05) only for LDL-C. The independent sample t-test analysis showed that white tea has higher effect in decreasing the lipids profile greater than green tea, however not significantly different (p>0,05). This study was proved that white tea is more potential than green tea to decreasing lipids profile of smokers.